GC-MS Characterization and evaluation of antioxidant potential and acute toxicity of Lupinus albus extracts - Rachida, Bouteldja; Hebib, Aggad; Hamza, Belkhodja; Zohra, Abdi Fatima; Radhouane, Doucene; Soher, Benhammouda Leila (Acta Biologica Szegediensis, 2025)
Lupinus albus L., a leguminous plant, plays a therapeutic role due to its richness in bioactive compounds, which have diverse applications in human health, as a green fertilizer, and as fodder. This study aims to characterize Lupinus albus extracts using Gas Chromatography-Mass Spectrometry (GC-MS) and determine their total phenolic content (TPC) and total flavonoid content (TFC). The antioxidant activity (via DPPH free radical scavenging assay) and acute toxicity in Wistar rats were also evaluated. Results showed that the ethanolic extract exhibited the highest TPC (59.66 ± 0.56 mg GAE/g), while the methanolic extract had the highest TFC (14.44 ± 0.20 mg QE/g). GC-MS analysis identified 20 compounds in the ethanolic extract, with the major constituents being lupanine (54.34%), valeric acid (22.26%), and isolinoleic acid (20.94%). The ethanolic extract demonstrated significant antioxidant activity, with an IC50 of 0.86 ± 0.01 mg/mL. Acute toxicity tests indicated that the L. albus extract contributed to decreased cholesterol and stabilized glycemia at a dose of 2000 mg/kg body weight.